Evaluasi Tingkat Kesukaan Panelis Terhadap Uji Organoleptik Ravioli Ayam Woku Berdasarkan Lima Atribut - Ida Hafidah; Alvin Aditya Ramadani (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Ravioli is a dish similar to dumplings, filled and wrapped in thin pasta dough. It is a staple in traditional Italian cuisine. In this study, the author collaborated with Cafe Sanji Eatery to create a pasta menu variant using Chicken and Woku. The research aims to determine the preference levels of panelists based on five evaluation attributes: appearance, aroma, color, texture, and taste, as well as to establish standard recipes and conduct a business analysis of the Chicken Woku Ravioli product. The methodology used in this study is research and development, involving five expert panelists from the faculty and 20 moderately trained student panelists. The results of the preference evaluation for the appearance, aroma, color, texture, and taste of Chicken Woku Ravioli showed: appearance 64% liked it very much, aroma 52% liked it very much, color 64% liked it very much, texture 68% liked it very much, and taste 52% liked it very much. Based on the research findings, the standard recipe consists of 50g chicken breast, 100g flour, 80g eggs, 10g chicken powder, 10g basil, 50g tomatoes, 25g garlic, 36g shallots, 30g lemongrass, 75g red chili, 9g bird’s eye chili, 4g pandan leaves, 2g turmeric leaves, 15g turmeric, 20g ginger, 5g salt, and 5g sugar. The business analysis results indicate a food cost of Rp 9,000 per serving with a selling price of Rp 22,500 per serving. The Chicken Woku Ravioli seller will break even (BEP) after selling 287 servings. To achieve a target margin of Rp 2,000,000 per month, the author plans to sell 435 servings per month. The seller aims for a profit margin of 40%. It is recommended to add more pasta shape variations to increase consumer interest.